Reproducibility of Clinico-histopathological Findings by Direct Immunofluorescence of Fixed, Paraffin Embedded Tissue Specimens for Diagnosis of Lichen Planus - Ali Reza Ghannadan; Maryam Seyedmajidi; Sara Mehrabi; Ozra Abdolabadi; Pouyan Aminishakib; Ali Bijani (Islamic Dental Association of Iran, 2015)
Background and Aim: Lichen planus (LP) is a chronic mucocutaneous disorder mediatd by the impaired immunity, in which the association of clinical and histopathological findings is necessary for a definite diagnosis. In case of discrepancy between the clinical and histopathological findings, use of adjunct diagnostic methods such as direct immunofluorescence (DIF) is recommended. This study sought to assess the reproducibility of clinico-histopathological findings byDIF of fixed, paraffin embedded tissue specimens for the diagnosis of LP. Materials and Methods: In this retrospective descriptive study, 49 oral (OLP) and cutaneous LP (CLP) specimens were subjected to DIF examination using fibrinogen, C3 and IgM. The intensity of staining was graded as 0, 1 or 2. Findings were compared in each group and between OLP and CLP groups using statistical tests. Results: Statistical analyses revealed a correlation between C3 and IgM expression (Spearman's rho: 0.697, P<0.001); this correlation was more prominent in CLP (Spear man's rho: 0.746, P<0.001). A correlation was observed between fibrinogen and IgM expression in OLP (Spearman's rho: 0.769, P=0.02). Statistical analysis with the Mann Whitney U test found no significant difference between OLP and CLP for the expression of C3 (P=0.3) or fibrinogen (P=0.5). But, a significant difference was noted between OLP and CLP for the expression of IgM (P=0.04). Conclusion: It seems that DIF examination of formalin-fixed, paraffin embedded tissue specimens using C3, fibrinogen and IgM does cannot adequately reproduce clinico-histopathological findings; although, combined use of C3 and IgM in CLP and IgM and fibrinogen in OLP specimens yielded higher reproducibility.